Segmental Frequency Modulated Probe for Non-Local Effect Reduction in a Pulse-Coded Brillouin Optical Time Domain Analyzer - Li, Zonglei; Zhou, Yin; Ye, Jia; Hua, Zexi; Yan, Lianshan (Frontiers in Physics, 2022)
Non-local effect is an important issue for a pulse-coded Brillouin optical time domain analyzer. Segmental frequency modulated probe, with a dedicated frequency step of half the natural Brillouin linewidth of the sensing fiber, is proposed to solve this issue. It can provide a wideband Brillouin gain as well as loss in the frequency band of the pump to alleviate pump distortions and thus non-local effects. This method can narrow the bit interval towards a level limited by the time of the Brillouin gain transition due to frequency switching, resulting in a bit interval as short as 900 ns for a 225 MHz frequency scanning range. A hot spot at the far fiber end is successfully detected even the probe power reaches -3 dBm under a cumulated Brillouin gain of 267.4%.